2013
DOI: 10.1111/asj.12140
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of reproductive and lifetime performances of Kagoshima Berkshire gilts and sows

Abstract: We investigated the reproductive and lifetime performances of Kagoshima Berkshire gilts and sows. We examined 20 605 parity records of 4419 pigs for 2008 to 2012 on a farrow-to-finish commercial farm. The mean parity (± SD) of all animals was 3.0 ± 2.1. For farrowing performance, the highest numbers of total pigs born and pigs born alive were found in sows with parities 5 and 6 and with parity 3-6, respectively (P < 0.05). Regarding weaning and mating performance, sows with parity 2 had the lowest preweaning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
3
14
1
3
Order By: Relevance
“…Therefore, it is important to consider the appropriate and optimal age at first farrowing and the weight and body condition for better reproductive performance in the next parities. The highest lifetime and per year productivity means for sow culled for old age and lowest productivity was obtained in the sows culled by miscellaneous and reproductive reasons, which agrees with the results of other authors Knauer et al 2012;Sasaki et al 2014;Ulguim et al 2014). This probably points to the fact that sows removed for reasons of old age had more parities, stay longer in the herd, and had the lowest non-productive days compared with sows culled by other reasons.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, it is important to consider the appropriate and optimal age at first farrowing and the weight and body condition for better reproductive performance in the next parities. The highest lifetime and per year productivity means for sow culled for old age and lowest productivity was obtained in the sows culled by miscellaneous and reproductive reasons, which agrees with the results of other authors Knauer et al 2012;Sasaki et al 2014;Ulguim et al 2014). This probably points to the fact that sows removed for reasons of old age had more parities, stay longer in the herd, and had the lowest non-productive days compared with sows culled by other reasons.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that sows that farrow the first time at an older age had lower LBA, NPF/Y, LPW, and NPW/Y (Le Cozler et al 1998;Babot et al 2003;Saito et al 2011;Koonawootrittriron et al 2012;Sasaki et al 2014). In Japan, Saito et al (2011) reported higher LBA and NPF/Y means in sows first service at 188-208 and 209-229 days of age (approximately 303-323 and 324-344 days of age of first farrowing, in this study), with 54.8 and 54.5 LBA, and 18.5 and 18.2 NPF/Y, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations